Amifostine treatment in patients with myelodysplastic syndrome - (:unkn) unknown (My University, 2005)
Myelodysplastic syndrome (MDS) is a clonal disorder that is characterized by peripheral cytopenia and the induction of apoptosis is thought to be partially responsible for pathological haematopoiesis in MDS. Amifostine is a cytoprotective and antioxidant agent, and it may prolong the survival of progenitor cells in MDS by delaying apoptosis. The study has been carried out with 9 MDS cases. Four of them were diagnosed as refractory anemia (MDS-RA), two as refractory anemia with ring sideroblasts (MDS-RARS) and the remaining three as refractory anemia with excess blasts (MDS-RAEB) according to the French-American-British (FAB) classification. Amifostine was given in a dose of 400 mg/m2, as an IV infusion administered in 5-6 minutes, three times a week for 4 consecutive weeks. Three of the cases (33.3%), two with MDS RARS and one with MDS-RA, showed a significant improvement in the number of total leukocyte, neutrophil and reticulocyte counts and a decrease in the requirement of erithrocyte transfusions. In clinically responsive cases, all hematological parameters returned back to pre-treatment values two weeks after the cessation of therapy. We conclude that Amifostine can be used in a selected group of patients with MDS-RA and MDS-RARS.
Keywords: Amifostine; Myelodysplastic syndrome